INSTITUTIONALIZATION PROBLEMS OF STATE NATIONAL POLICY OF THE RUSSIAN FEDERATION - Tetuev, Alim Inzrelovic (History, Archeology and Ethnography of the Caucasus, 2017)
The process of development of state national policy in the Russian Federation at various stages of modernization reforms is analyzed in the article. The author reviews the results of implementation of the Concept of State National Policy of the Russian Federation on institutionalization of interethnic relations and creation of conditions for ethnocultural and ethnopolitical development ofpeoples and studies dynamics and tendency of development of interethnic relations at the present stage. The analysis of national processes in the Russian society allows concluding that since the beginning of the 21 st century there has been a trend towards social and political stabilization. However, it must be admitted that in the 1990s, Russian national policy was characterized by a retarded factor and a slow reaction to arising problems and growing conflicts, by a lack of integrated approaches to solving problems. The measures for implementation of the «Strategy of State National Policy of the Russian Federation for the Period until 2025» and the Federal Target Program “Strengthening of the Unity of the Russian Nation and Ethnocultural Development of the Peoples of Russia” are analyzed in the article. The author identifies socio-economic factors that contribute to ethnopolitical tensions in the regions and determines measures for further economic, social and cultural development of the region. An important condition for harmonization of interethnic relations between the peoples of Russia is restoration and strengthening of their interrelations in cultural sphere, strengthening of Russian spirituality, Islamic and Orthodox civilizations
Keywords: national policy; interethnic relations; ethnocultural development; normative and legal acts; strategy; concept; socio-economic factors